2015
DOI: 10.1186/s13049-015-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

The formation and design of the TRIAGE study - baseline data on 6005 consecutive patients admitted to hospital from the emergency department

Abstract: BackgroundPatient crowding in emergency departments (ED) is a common challenge and associated with worsened outcome for the patients. Previous studies on biomarkers in the ED setting has focused on identification of high risk patients, and and the ability to use biomarkers to identify low-risk patients has only been sparsely examined. The broader aims of the TRIAGE study are to develop methods to identify low-risk patients appropriate for early ED discharge by combining information from a wide range of new inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…However, one study by Barfod et al 12 16 investigated the relationship between the first Danish modified ADAPT model and in-hospital mortality in a comparable unselected ED patient group. The study had a similar distribution of patients to ADAPT categories as ours to DEPT categories, but with fewer patients in the orange triage group and more patients in the red triage group 9. The study found an overall 28-day mortality which was equal to the overall 30-day mortality found in our cohort.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, one study by Barfod et al 12 16 investigated the relationship between the first Danish modified ADAPT model and in-hospital mortality in a comparable unselected ED patient group. The study had a similar distribution of patients to ADAPT categories as ours to DEPT categories, but with fewer patients in the orange triage group and more patients in the red triage group 9. The study found an overall 28-day mortality which was equal to the overall 30-day mortality found in our cohort.…”
Section: Discussionsupporting
confidence: 72%
“…All data derive from the ‘Triage study’, which is a prospective observational cohort study previously described in detail elsewhere 9. The aim of the study was to optimise risk stratification and develop methods to identify low-risk patients appropriate for early ED discharge.…”
Section: Methodsmentioning
confidence: 99%
“…La deuxième filière concerne des patients admis par les urgences ou à partir d'un secteur d'hospitalisation conventionnelle consécutivement à la survenue d'une complication. On estime que 3 % des patients admis aux urgences sont orientés vers les soins critiques, unités de surveillance continue (USC) ou réanimation [21]. L'enjeu est ici de dépister précocement les signes de gravité de ces patients afin de les affecter dans la structure qui leur est adaptée.…”
Section: Filière Des Urgences Et Hospitalisation Médecinechirurgie-obunclassified
“…The cut-off points for vital signs (Fig. 1 ) of CTA were calculated using the results of the TRIAGE database [ 24 ]. This was done by defining either the 10 % highest (e.g.…”
Section: Designmentioning
confidence: 99%
“…Recently, data from ED visits have been collected over a period of 3 months at North Zealand Hospital giving a complete cohort of 6 000 patient ED visits [ 24 ]. This study confirmed earlier studies’ conclusion that vital signs at admission are strong predictors of acute patient outcomes [ 21 ], and further demonstrated that a quick clinical assessment of patients by phlebotomists and medical students was superior in predicting 30-day mortality than formalized DEPT triage [ 25 ].…”
Section: Introductionmentioning
confidence: 99%